A importância de ações estratégicas de gestão de pessoas no manejo do estresse e de estressores ocupacionais - Benetti, Caroline [UNESP]; Magri, Natália [UNESP]; Campos, Dinael Correa de [UNESP]; Goulart Júnior, Edward [UNESP; Camargo, Mário Lázaro [UNESP]; Feijó, Marianne Ramos [UNESP] (My University, 2014)
The introducing of new technologies at work contexts forces the contemporary organizations to search new structures and productive processes, as well as new management models, mainly personnel management. A strong pressure by positive results can favour health problems concerning to stress, which is caused by a highly competitive environment; studies reveals that stress is a present reality at organizations nowadays. The presence of stress on workers cause harm to organizations (due to absenteeism increasing, turnover, interpersonal conflicts, etc.) and individuals, whose life quality can be decreased. This text intends to highlight the importance of identifying stress presence on workers and eventual stressors at workplaces, with the objective of, through management strategies, propose interventions guided to promote occupational health and welfare. Identifying eventual stressors at workplaces becomes an essential task, because those signs predispose the stress presence on workers. Therefore, discovering them is a strategic way to preventing and managing of occupational stress. This text also proposes to show some personnel management strategies which can favour the prevention of occupational stressors, as well as interventions on them.

A introdução de novas tecnologias nos contextos de trabalho obriga as organizações contemporâneas a buscarem novas estruturas e processos produtivos como também novos modelos de gestão, sobretudo de gestão de pessoas. A forte cobrança por resultados positivos podem favorecer problemas de saúde referente ao estresse causado por um ambiente altamente competitivo; estudos revelam que o estresse é uma realidade presente nas organizações na atualidade. A presença do estresse em trabalhadores traz prejuízos tanto para as organizações (com o aumento do absenteísmo, rotatividade, conflitos interpessoais, etc.) como para os indivíduos que podem ter sua qualidade de vida reduzida. O texto apresentado pretende destacar a importância da identificação da presença do estresse em trabalhadores e a identificação dos possíveis estressores do ambiente de trabalho, visando, mediante estratégias de gestão, a preposição de intervenções voltadas à promoção da saúde e bem estar ocupacionais. A identificação dos possíveis estressores nos ambientes de trabalho torna-se fundamental, uma vez que eles predispõem a presença do estresse nos trabalhadores. Logo, identificalos torna-se estratégico para a prevenção e manejo do estresse ocupacional. O texto também se propõe a apresentar algumas estratégias de gestão de pessoas que podem favorecer a prevenção e intervenção dos estressores ocupacionais.
The importance of strategic actions of personnel management at administration of occupational stress and stressors
Keywords: Personnel management; Occupational stress; Occupational health; Gestão de pessoas; Estresse ocupacional; Saúde ocupacional